Rīgas Politehnikuma absolvents un mācībspēks – profesors Jozefs Rončevskis (1864–1921) (Inženierzinātņu un augstskolu vēsture, 2018)
Raksts iepazīstina ar Sanktpēterburgā dzimušā Jozefa Rončevska (1864–1921) – pazīstamā tēlnieka, arhitektūras vēsturnieka, pedagoga Konstantīna Rončevska brāļa – zinātnisko un pedagoģisko darbību, kas līdz šim ir bijusi maz zināma un neizpētīta. J. Rončevskis ir Rīgas Politehnikuma Ķīmijas tehniskās nodaļas absolvents (1889) un mācībspēks (1893–1896), papildinājis zināšanas metalurģijā Vācijā, strādājis par profesoru un bibliotekāru Tomskas Tehnoloģiskajā institūtā (1900–1905), veicis pētījumus metalurģijā, bijis pirmais Latvijas Izglītības ministrijas Mazākuma tautību departamenta Poļu izglītības pārvaldes priekšnieks (1921).Joseph Ronczewski (1864–1921) - Alumnus and Docent of the Riga PolytechnicThe article introduces readers to Joseph Ronczewski (1864–1921) who was born in St. Petersburg. He is the brother of the well-known sculptor and specialist of the history of architecture Professor Konstantin Ronczewski. Until now, Joseph Ronczewski had been in the shadow of his brother Konstantin and his name is not well known, therefore the research about his life has been done. He is an alumnus of the Department of Chemistry of Riga Polytechnic (he graduated in 1889) and from 1893 to 1896, was an Assistant with the same Department. He perfected his knowledge in steel industry in Germany and later was a professor and librarian with the Institute of Technology (1900–1905) in Tomsk. He carried out his research in the sector of metallurgy. During World War I, he was in Russia and after the war moved to Latvia. In February 1921, he was the first to head the Department of the Polish Minority of the Ministry of Education of Latvia. He died in December 1921.Keywords: Joseph Ronczewski, Riga Polytechnic, Polish people in Latvia.Выпускник и педагог Рижского политехникума профессор Иосиф Рончевский (1864–1921)В статье описан жизненый путь родившегося в Санкт-Петербурге Иосифа Рончевского (1864–1921), брата известного скульптора, историка архитек- туры, профессора Константина Рончевского. Сведений о жизни Иосифа Рончевского до сих пор было мало, но в процессе исследования удалось узнать более подробные факты о семье Рончевских. Иосиф Рончевский окончил Химическое отделение Рижского политехникума (1889) и рабо- тал преподователем в своей алма матер ( 1893–1896). П отом о н б ыл откомандирован на 3 года в Германию для изучения металлургии и под- готовки к профессорской деятельности в Германии, работал профессором и библиотекарем Томского технологического института (1900–1905), про- водил исслeдования в области металлургии. После Первой мировой войны он вернулся в Латвию и в феврале 1921 года стал первым начальником Польского управления по образованию при Департаменте меньшинств Министерства образования Латвии, но многое сделать не удалось – уже в декабре того же года окончился его жизненый путь.Ключевые слова: Иосиф Рончевский, Р ижский п олитехникум, п оляки в Латвии.